Chinese Taoist Cognitive Therapy for Symptoms of Depression and Anxiety in Adults in China: A Systematic Review and Meta-Analysis - Ding, Yudan; Wang, Li; Chen, Jindong; Zhao, Jingping; Guo, Wenbin (Frontiers in Psychology, 2020)
Background: Chinese Taoist cognitive therapy (CTCT), a culture-oriented psychological therapy for Chinese mental well-being, has been proposed for decades. However, the evidence for its effects is unclear. This study aimed to systematically assess the effect of this therapy on symptoms of depression and anxiety in Chinese adults. Methods: Relevant studies were searched from major electronic databases through November 2018 without language limits. Several search terms used include “anxiety” OR “depression” AND “Taoism” OR “Daoism” OR “Chinese Taoist Cognitive Therapy.” A total of 11 clinical trials focusing on CTCT were included in this meta-analysis. Random-effects meta-analytical models were conducted. Heterogeneity and publication bias were also explored. Results: Eight clinical trials for 580 subjects were included. The majority of these studies explored samples with depressive symptoms. Overall, CTCT significantly reduced depressive symptoms with a small positive effect (SMD = 0.16, 95% CI: −0.36–0.68). Medium-to-large effect sizes were observed across individuals with clinical or non-clinical depression and chronic physical diseases (SMD = 0.70, 95%CI: 0.27–1.13 and SMD = 0.72, 95%CI: 0.09–1.35, respectively). However, the effectiveness for anxiety symptoms remains debatable. Conclusions: Our findings hold promise that CTCT can help reduce depressive symptoms in Chinese adults, including patients with chronic physical diseases and clinical or non-clinical depression. Our findings may be generalized to Chinese communities in other countries.